Feasibility of Lexicon Reading Materials of Labuhanbatu Utara Local Wisdom in Senior High School (SMAN) 1 Kualuh Selatan - Kursitasari Kursitasari; Khairil Ansari; Evi Eviyanti (BIRCU, 2019)
This study aims to discuss about feasibility of lexicon reading materials of Labuhanbatu Utara local wisdom in senior high school (SMAN) 1 Kualuh Selatan. The research location will be carried out in Labuhanbatu Utara regency precisely in Kualuh Selatan Sub-District consisting of twelve villages. The result shows that Labuhanbatu Utara's local wisdom lexicon is obtained based on six types of local wisdom, namely the quality of bordah kualuh art, endeng-endeng art, sinandong art, cenggok-cenggok tradition, mengupah-upah tradition, and Labuhanbatu Utara’s food. The six types of local wisdom above can be grouped into two types of arts and traditions. From the results of the research on noun lexicons there are 72 lexicons of all of Labuhanbatu Utara's local wisdom, and there are 45 lexicons from all the local wisdom of Labuhanbatu Utara.